2010
DOI: 10.2214/ajr.09.2707
|View full text |Cite
|
Sign up to set email alerts
|

MR-Directed (“Second-Look”) Ultrasound Examination for Breast Lesions Detected Initially on MRI: MR and Sonographic Findings

Abstract: MR-directed ultrasound of MRI-detected lesions was useful for decision making as part of the diagnostic workup. Malignant lesions were likely to have an ultrasound correlate, especially when they presented as masses on MRI. However, the sonographic findings of these lesions were often subtle, and careful scanning technique was needed for successful MRI-ultrasound correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
121
5
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(146 citation statements)
references
References 16 publications
12
121
5
8
Order By: Relevance
“…However, with SLUS, it is more difficult to detect lesions with negative results on the initial US. Also, most lesions larger than 16 mm were non-mass-like enhancements that were more difficult to detect than masses (10). There was no statistically significant correlation between the cancer rate and the lesion type.…”
Section: • January-february 2015 • Diagnostic and Interventional Radimentioning
confidence: 83%
See 3 more Smart Citations
“…However, with SLUS, it is more difficult to detect lesions with negative results on the initial US. Also, most lesions larger than 16 mm were non-mass-like enhancements that were more difficult to detect than masses (10). There was no statistically significant correlation between the cancer rate and the lesion type.…”
Section: • January-february 2015 • Diagnostic and Interventional Radimentioning
confidence: 83%
“…In a previous study, targeted US identified 65 of 73 additionally detected enhancing lesions (89%), and eight lesions (11%) were not visible on targeted US (14). Shin et al (11) reported that the detectability rate of SLUS was 71% (27/38), and Abe et al (10) reported that US correlation was made in 115 of 202 additionally detected enhancing lesions (57%). In this study, 72 of 85 unexpected enhancing lesions (85%) were detected on SLUS, demonstrating a relatively high level of detectability compared with the previous studies.…”
Section: • January-february 2015 • Diagnostic and Interventional Radimentioning
confidence: 94%
See 2 more Smart Citations
“…This requires not only to be familiar with (supine) breast US but also with (prone) breast MRI as well as with the different lesion location at the two imaging techniques. Six recent studies reported percentages of US correlate for initially MR-detected findings variable from 46% to 82% [17][18][19][20][21][22]. Pooling their results, we have a total of 1,208 findings, 759 of them with a US correlate (63%).…”
Section: Additional Findings At Preoperative Mri a Simple Golden Rulmentioning
confidence: 89%